Development of a core competence model for improving medical college students’ ability in respond to public health emergencies - Liu, Fengqiong; Huang, Shuqian; Chen, Fa; Yang, Suhua; Wu, Lixin; Lin, Yulan; He, Baochang; Hu, Zhijian (Frontiers in Public Health, 2025)
BackgroundCore competences has been developed for public health professionals worldwide. However, there is no core competences framework as to how to evaluate public health professionals and undergraduate students’ ability to respond to public health emergencies.ObjectivesTo develop a framework of core competences in public health emergencies for education of medical college student who majored in public health. To assess the knowledge and skill level of undergraduate students with public health background in respond to health emergency event and get to known the training needs.MethodsThe Delphi method was applied to develop an agreed list of competences, which was followed by the construction of a competences framework in public health emergencies. A questionnaire consists of items that was derived from the list of competency statements developed by Delphi scoring to quantitatively report the knowledge and practical skill level and training needs of medical college students of public health background in public health emergencies.ResultsAn agreed set of core competences containing 43 statements was derived from the first and second Delphi scoring steps which can be grouped into four domains: intellectual competences, practical competences, behavioral competences, personnel and motivation. A total of 441 undergraduate students with public health background participated in the survey. The average performance of intellectual and practical competences is 3 in a 5-point scale, which equals 60 converted to 100 points. A better performance was observed in indicators of behavioral competences and personnel and motivation with an average score of 4 for most of the items, which equals 80 converted to 100 points. Admission year and sex are significantly related to competency performance of all domains with β value of −0.141 (p = 0.003) and − 0.237 (p < 0.001) for the overall performance.ConclusionA framework of 43 core competences was developed, which covered both technical and general competencies in public health emergencies and represent the current competence demands of public health work force to be qualified for their job roles in public health emergencies for the local government in Fujian province. The concordance rate regarding to score of importance of the core competences are all >80% in both the first and second round Delphi survey, suggesting considerable reliability of the framework.